2016
DOI: 10.3402/jchimp.v6.32170
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of symptoms with sleep-stage abnormalities in obstructive sleep apnea-hypopnea syndrome

Abstract: BackgroundPatients with obstructive sleep apnea-hypopnea syndrome (OSAHS) present with a variety of sleep-related symptoms. In polysomnography, sleep architecture is almost always abnormal, but it is not known which of the sleep-stage abnormalities are related to symptoms. Finding key sleep-stage abnormality that cause symptoms may be of therapeutic importance to alleviate symptoms. So far the mainstay of treatment is continuous positive airway pressure (CPAP)/bi-level positive airway pressure (BIPAP) therapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
1
10
2
1
Order By: Relevance
“…Sleep architecture is estimated by leveraging wearable sensors or smartwatches with machine learning methods and its effect on OSA screening is observed in [72,73]. Specifically, stage 1 and stage 3 sleep exhibited anomalous behavior in the case of OSA patients, as stated in [74][75][76]. Interestingly, the findings of our presented work does not reveal strong predictive powers when using the features of sleep stages (stage 1, stage 2, stage 3 and REM) as well as sleep duration metrics.…”
Section: Discussionmentioning
confidence: 78%
“…Sleep architecture is estimated by leveraging wearable sensors or smartwatches with machine learning methods and its effect on OSA screening is observed in [72,73]. Specifically, stage 1 and stage 3 sleep exhibited anomalous behavior in the case of OSA patients, as stated in [74][75][76]. Interestingly, the findings of our presented work does not reveal strong predictive powers when using the features of sleep stages (stage 1, stage 2, stage 3 and REM) as well as sleep duration metrics.…”
Section: Discussionmentioning
confidence: 78%
“…The study by Buysee et al [ 11 ] revealed that symptoms assessed by the ESS and PSQI are not correlated with objective sleep features measured by PSG. Basunia et al [ 35 ] reported that among patients with OSA, symptoms such as excessive fatigue or sleepiness, falling asleep during the day, waking up tired, trouble paying attention, snoring, and insomnia were significantly related to a decreased percentage of N3 sleep. Conversely, in our study, increasing N3 percentages of total sleep time were linked to higher risks of poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…It can increase the expression of inflammatory cytokines such as IL-18 and IL-6 and produce synergistic amplification [15]. IL-6 is a member of the IL-12 family, secreted mainly by activated macrophages and dendritic cells, and has an important role in the maintenance of Th17 cell activation [18]. It stimulates the proliferation of Th17 cells and the secretion of IL-18, and promotes the production of chronic inflammatory factors and proinflammatory chemokines in activated Th17 cells.…”
Section: Discussionmentioning
confidence: 99%